2019
DOI: 10.1101/639088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel L-Serine Exporter and Its Positive Regulator in Corynebacterium glutamicum

Abstract: 19Exporters play an essential role in the fermentative production of amino acids. In 20 Corynebacterium glutamicum, ThrE, which can export L-threonine and L-serine, is the 21 only identified L-serine exporter so far. In this study, a novel L-serine exporter NCgl0580 22 was identified and characterized in C. glutamicum ΔSSAAI (SSAAI), and named as SerE 23 (encoded by serE). Deletion of serE in SSAAI led to a 56.5% decrease in L-serine titer, 24 whereas overexpression of serE compensated for the lack of serE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The results showed that SR had the lowest heritability using both ST-GBLUP (h 2 = 0.220) and ST-BayesCπ (h 2 = 0.263), which is consistent with previous reports in American Simmental cattle (ranging from 0.12 to 0.36) [36]. Lower heritability estimates were expected as this trait may be controlled by many genes [5], whereas the high heritability for REWT and REA may indicate a strong effect from major genes [37]. For the MT method, the strongly positive correlations were observed between SWT-CWT, SR-REWT, and CWT-REWT, which may indicate that these traits were controlled by genes with pleiotropic effects or are in strong Linkage disequilibrium (LD) [38,39].…”
Section: Heritability and Genetic Correlation Estimationsupporting
confidence: 89%
“…The results showed that SR had the lowest heritability using both ST-GBLUP (h 2 = 0.220) and ST-BayesCπ (h 2 = 0.263), which is consistent with previous reports in American Simmental cattle (ranging from 0.12 to 0.36) [36]. Lower heritability estimates were expected as this trait may be controlled by many genes [5], whereas the high heritability for REWT and REA may indicate a strong effect from major genes [37]. For the MT method, the strongly positive correlations were observed between SWT-CWT, SR-REWT, and CWT-REWT, which may indicate that these traits were controlled by genes with pleiotropic effects or are in strong Linkage disequilibrium (LD) [38,39].…”
Section: Heritability and Genetic Correlation Estimationsupporting
confidence: 89%
“…Recent studies have identified more relative major genes and candidate mutations using large-scale genome sequencing and multi-omics technology. For example, in a study of growth and body size, Karim et al reported that a variant in promoter of PLAG1 was causal in bovines [202]; in a study of meat quality, Wang et al detected that SCD had a significant effect on muscular fatty acid composition, especially for C14:1 cis-9 [177]; in a study of reproductive traits, Fang et al provided evidence indicating ZNF613 as a putative candidate T A B L E 2 Summary of GWAS related to farm animals in past 5 years.…”
Section: Cattlementioning
confidence: 99%
“…The addition of CaCO 3 enhanced the compatibility between PBAT and PLA, improved the thermal stability, tensile properties, complex viscosity, energy storage modulus and loss modulus of the composites and reduced the crystallinity of the composites. 115 As PLA also thermally degrades at higher temperatures, the addition of magnesium oxide (MgO) to PLA/PBAT composites can reduce the thermal degradation temperature and activation energy of the composites. 115 Using the solution blending method to prepare PLA/PBAT/MgO composites, the addition of MgO can enhance the initial thermal decomposition temperature of PLA/PBAT/MgO composites.…”
Section: Biodegradable Polymersmentioning
confidence: 99%
“…115 As PLA also thermally degrades at higher temperatures, the addition of magnesium oxide (MgO) to PLA/PBAT composites can reduce the thermal degradation temperature and activation energy of the composites. 115 Using the solution blending method to prepare PLA/PBAT/MgO composites, the addition of MgO can enhance the initial thermal decomposition temperature of PLA/PBAT/MgO composites. 84 During melt extrusion of PLA/PBAT composites, melt flow rate, softening temperature and other factors affect the processing fluidity of the composite, which in turn affects the base shape of the blend.…”
Section: Biodegradable Polymersmentioning
confidence: 99%